Do Board Multiple Directorships and ESG Score Drive Firm Value? Study of Non-Financial Companies in Thailand - Sany Sany; Caroline Novica; Cynthia Valentina (Jurnal Akuntansi dan Keuangan, 2024)
This study intends to demonstrate the impact of board busyness through board multiple directorships and ESG scores towards firm value in Thailand within the period of 2018-2022. Theoretical frameworks such as the resource dependence theory and stakeholder theory explicate the two hypotheses developed for busy directors and ESG score. A director has multiple directorships when he/she has more than three board roles in other publicly listed firms, excluding private organizations and foundations. This research’s population are listed non-financial firms in Thailand Stock Exchange that has ESG score in Refinitiv database for five consecutive years during 2018 to 2022. Final data sample are 28 non-financial companies resulting in 140 observations. Directorship and board size were hand collected from annual reports. Panel data regression with random effect model is used, and results show that there is no association between multiple directorship and firm value. On the other hand, ESG shows a positive and significant relationship towards firm value. This research supports the belief that ESG scores have a notable impact on firm value based.